Um surto de coccidiose em perdizes (Rhynchotus rufescens), criadas em cativeiro, por Eimeria rhynchoti Reis e Nóbrega, 1936 (Apicomplexa: Eimeriidae). - Freitas, Fagner Luiz da C; Almeida, Katyane de S; do Nascimento, Adjair A; Machado, Celio R; Machado, Rosangela Z (My University, 2006)
Eimeria rhynchoti is redescribed parasitizing partridge (Rhynchotus rufescens), reared in captivity, from Jaboticabal City, São Paulo State, Brazil. Sporulation takes place in 48 hours, the shape of oocysts found vary from spherical to elliptic with 23.01 micro +/- 1.57 of length by 21.0 micro +/- 1.78 of width. The microple, polar cap and residuum of the oocysts were absent. The oocyst wall, measures 2.2 micro +/- 0.31 of thickness, is composed by two smooth layers; the polar granule is present. The sporocysts length was 15.03 mm +/- 2.12 by 8.08 mm +/- 0.84 of width vary from elliptic to elongate. Sporocyst wall slender with is fine and Stieda body; the residue found in form of several smaller granules spherical compacts. The sporozoites are contrary extending along the sporocysts wall possessing refracts body of easy visualization.
An outbreak of coccidiosis in partridge (Rhynchotus rufescens), reared in captivity, by Eimeria rhynchoti Reis and Nobrega, 1936 (Apicomplexa: Emeriidae)
Keywords: animal; animal disease; bird disease; coccidiosis; Eimeria; epidemic; female; Galliformes; male; Animals; Bird Diseases; Coccidiosis; Disease Outbreaks; Female; Male